AKIBAT HUKUM PEMBERIAN SURAT KETERANGAN SAKIT TERHADAP PASIEN - Meivy Isnoviana; Suhandi Suhandi (Perspektif, 2005)
Doctors who have Practice License are authorized to issue notification letters taking form of healthy letter; sick letter; the letter granting must be in line with medical standards, yet if the letters are made not based on actual conditions and the notification letters can harm other parties, thusly the doctor’s conduct can be sued by any party who suffer the loss, therefore, the doctor can be subject to sanction from Honour Council of Medical Ethical Code and can result in legal consequences either civil or criminal laws.